A multidisciplinary integrated approach using Pachygrapsus marmoratus to assess the impact of port activities on mediterranean marine protected areas. (January 2023) - Caliani, Ilaria; Cannicci, Stefano; Pretti, Carlo; Baratti, Mariella; Contini, Ginevra; Vitale, Matteo; Casini, Silvia; Fossi, Maria Cristina; Iannucci, Alessio; Fratini, Sara
Abstract: The establishment of marine protected areas is considered the main global strategy to halt the loss of marine biodiversity. Since most of marine areas are open systems, this form of habitat protection cannot prevent their contamination due to human activities performed outside of their borders. Innovative approaches to assess the health status of protected marine habitats are therefore needed. Here we developed a multidisciplinary approach that combines ecological characteristics, bioaccumulation of inorganic and organic pollutants, cell damage (micronuclei frequency, nuclear alterations and LPO) and enzymatic (AChE, CAT, IDH, LDH, GST and CAT) markers focused on an intertidal brachyuran crab, Pachygrapsus marmoratus, to assess the impacts of contaminant exposure on Mediterranean coastal habitats. As study sites we selected two protected areas and two sites within industrial ports of the Ligurian Sea. Our results showed that the selected crab species is an excellent bioindicator. Individuals collected in sites with the highest levels of heavy metal pollution showed the highest signals of stress responses at both cellular and enzymatic levels, coupled with a high incidence of the parasite Sacculina carcini, a signal of impairment of their standard development and reproduction cycle. We could also prove that one of the selected marine protected areas showed the same intensity of impact as its adjacent port site. Our multidisciplinary approach proved to be a valuable tool to assess the environmental quality and health of protected and disturbed Mediterranean coastal environments and to inform efficient management and protection schemes for such habitats. Graphical abstract: Image 1 Highlights: Ecological, chemical and biomarker data were recorded in an intertidal crab. Populations from two marine protected areas and two adjacent ports were selected. Oxidative stress and genotoxicity biomarkers were higher in crabs from polluted sites. One protected population showed stress related responses similar to adjacent port one. Our integrated approach showed to be reliable for efficient management for coastal habitats.